Stabilisation of grid assistance for a renewable hydrogen generation system by min-projection strategy - Garcia Clua, Jose Gabriel (2016)
Control of grid assistance is proposed in this study for a renewable hydrogen generation system of simple and robust structure. Here, the grid connection serves the dual purpose of minimising the effect of wind power variations in the electrolyser supply as well as maximising the hydrogen production. To regulate the electrolyser current at its rated value, a cascade control scheme is posed. The feedback loop which commands the grid converter switching is of interest for the design. The min-projection strategy that stabilises a switched affine system is applied as the switching law. The analysis of switched equilibria and their stability is done by employing the concepts of Filippov inclusion and common Lyapunov function, respectively. The obtained theoretical results are corroborated by numerical simulation.